DENTAL DISEASE IDENTIFICATION USING FUZZY INFERENCE SYSTEM - Andi Maulidinnawati A K Parewe; Wayan Firdaus Mahmudy (Journal of Environmental Engineering and Sustainable Technology, 2016)
In the field of dentistry there are many types / variants of dental diseases emerging that make doctors and medical students may face difficulty to identify of dental diseases. In this study, a computers application is developed as a tool for doctors and medical students to identify various types of dental disease accurately. Fuzzy inference system is used an identification method. The method uses symptoms of dental disease as input parameters. Dental disease identification system using Fuzzy Inference System with Minmax. The parameters used to limit the fuzzy membership functions based on expert opinion. The accuracy of the system is calculated by comparing the output system with expert judgment. Experimental results show that the system is built to produce 85% accuracy.